Ulos as Batak Cultural Wisdom Towards World Heritage - Rizki Ananda Hasibuan; Saefur Rochmat (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
Ulos as one of Indonesia's intangible cultural heritages is the fruit of thought and the result of high quality art as an ancestral heritage that must be preserved. The sacred value of ulos is a picture of the inner world of the Batak people. Each ulos has a meaning and purpose between the giver and recipient of ulos. The stipulation of ulos as an intangible cultural heritage of Indonesia is a new hope to move towards a world heritage. The purpose of writing this article is to describe ulos as a Batak cultural identity that has been established as an intangible cultural heritage of Indonesia accompanied by efforts to become a world heritage, in addition to increasing literacy about Ulos. The method used in this paper is descriptive method, by describing the existing phenomena and collecting literature study data. Under the auspices of UNESCO as the world organization that houses cultural heritage, every country is obliged to report and propose new cultural heritage to become world heritage on a regular basis. With this step, Ulos under the auspices of the Aceh BPNB (Cultural Value Conservation Center) continues to strive and strive to be registered in accordance with the requirements of a cultural heritage to become a world heritage.